2005
DOI: 10.1253/circj.69.1535
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Progression and Morbidity in Patients With Aortic Stenosis on Chronic Dialysis

Abstract: AS appeared to progress rapidly in CD patients and therefore early aortic valve replacement may be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 25 publications
1
47
0
1
Order By: Relevance
“…LA and LV dimensions were normalized by body surface area (BSA: LAD index, LVDd index and LVDs index, respectively). The LV outflow tract (LVOT) diameter was measured in the parasternal long-axis view in mid-systole, and then converted to LVOT area: π×(0.5×LVOT diameter) 2 . 6,7 LV volume and ejection fraction (EF) were assessed using the biplane Simpson's rule.…”
Section: Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…LA and LV dimensions were normalized by body surface area (BSA: LAD index, LVDd index and LVDs index, respectively). The LV outflow tract (LVOT) diameter was measured in the parasternal long-axis view in mid-systole, and then converted to LVOT area: π×(0.5×LVOT diameter) 2 . 6,7 LV volume and ejection fraction (EF) were assessed using the biplane Simpson's rule.…”
Section: Echocardiographymentioning
confidence: 99%
“…Doppler-derived stroke volume (SV) was calculated as the product of the LVOT area and the LVOT velocity-time integral (VTI) obtained on pulsed Doppler, and was normalized by BSA (SV index). LV mass was calculated using the area-length method and was normalized by BSA (LV mass index), and LV geometries were classified into 4 types: (1) normal, relative wall thickness (RWT; 2×PWT/LV diastolic diameter) <0.42 and LV mass index <88 g/m 2 for female subjects and <102 g/m 2 for male subjects; (2) concentric remodeling, PWT >0.42 and LV mass index <88 g/m 2 for female subjects and <102 g/m 2 for male subjects; (3) eccentric hypertrophy, PWT <0.42 and LV mass index >88 g/m 2 for female and >102 g/m 2 for male subjects; and (4) concentric hypertrophy, PWT >0.42 and LV mass index >88 g/m 2 for female subject and >102 g/m 2 for male subjects. 8 The ratio of peak early (E) to late (A) diastolic transmitral flow velocity (mitral E/A) and deceleration time were calculated using pulsed Doppler echocardiography.…”
Section: Echocardiographymentioning
confidence: 99%
“…[1][2][3][4] In particular, recent studies have shown that any stage of renal dysfunction (mild to severe) is an independent risk factor for short-and long-term mortality among patients with myocardial infarction (MI), even after administration of fibrinolytics. [5][6][7][8] Moreover, it has been demonstrated that impaired renal function is associated with poorer clinical outcome after either percutaneous coronary intervention or coronary artery bypass graft surgery.…”
mentioning
confidence: 99%
“…[17][18][19] Several studies have suggested that several risk factors associated with atherosclerotic disease have been associated with degenerative AV, including age, gender, smoking, hyperlipidemia, hypertension and diabetes. [20][21][22][23] Risk factors in patients with degenerative AS were similar to those of CAD in the elderly population. A large number of patients with AS have concomitant CAD.…”
Section: Discussionmentioning
confidence: 70%